Design and rationale of the EMPA‐VISION trial: investigating the metabolic effects of empagliflozin in patients with heart failure. (6th May 2021) - Hundertmark, Moritz J.; Agbaje, Olorunsola F.; Coleman, Ruth; George, Jyothis T.; Grempler, Rolf; Holman, Rury R.; Lamlum, Hanan; Lee, Jisoo; Milton, Joanne E.; Niessen, Heiko G.; Rider, Oliver; Rodgers, Christopher T.; et al.
Abstract: Aims: Despite substantial improvements over the last three decades, heart failure (HF) remains associated with a poor prognosis. The sodium‐glucose co‐transporter‐2 inhibitor empagliflozin demonstrated significant reductions of HF hospitalization in patients with HF independent of the presence or absence of type 2 diabetes mellitus in the EMPEROR‐Reduced trial and cardiovascular mortality in the EMPA‐REG OUTCOME trial. To further elucidate the mechanisms behind these positive outcomes, this study aims to determine the effects of empagliflozin treatment on cardiac energy metabolism and physiology using magnetic resonance spectroscopy (MRS) and cardiovascular magnetic resonance (CMR). Methods and results: The EMPA‐VISION trial is a double‐blind, randomized, placebo‐controlled, mechanistic study. A maximum of 86 patients with HF with reduced ejection fraction ( n = 43, Cohort A) or preserved ejection fraction ( n = 43, Cohort B), with or without type 2 diabetes mellitus, will be enrolled. Participants will be randomized 1:1 to receive either 10 mg of empagliflozin or placebo for 12 weeks. Eligible patients will undergo cardiovascular magnetic resonance, resting and dobutamine stress MRS, echocardiograms, cardiopulmonary exercise tests, serum metabolomics, and quality of life questionnaires at baseline and after 12 weeks. The primary endpoint will be the change in resting phosphocreatine‐to‐adenosine triphosphate ratio, as measured by 31 Phosphorus‐MRS. Conclusions: EMPA‐VISION is the first clinical trial assessing the effects of empagliflozin treatment on cardiac energy metabolism in human subjects in vivo . The results will shed light on the mechanistic action of empagliflozin in patients with HF and help to explain the results of the safety and efficacy outcome trials ( EMPEROR‐Reduced and EMPEROR‐Preserved ).